RISK FACTORS FOR ISCHAEMIC STROKE: CORRELATON OF GENDER AND AGE WITH STROKE SEVERITY AND PATIENT OUTCOME - Gashpar, Glorija; Angelova, Aleksandra; Arsovska, Anita; Rexhepi, Arbana (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
The risk of stroke exists regardless of gender, age, co-morbidities and lifestyle. Yet, research points out to significant differences concerning the severity of stroke and its functional outcome, correlated to gender, age as well as co-morbidities. The aim of our study is to analyse the stroke-related risk factors, as well as to createa correlation with gender and age respecting stroke severity and patient outcome. We conducted a retrospective analysis of 157 patients hospitalized at the Department for Urgent Neurology, at the University Clinic for Neurology in Skopje, N. Macedonia, during the period of October 2019- October2020.  All of the included patients were diagnosed with ischemic stroke, confirmed by a computed tomography (CT scan) of the brain. Patientâ€™s risk factors (hypertension, diabetes, atrial fibrillation, etc.) were analyzed in relation to gender (men and women) and age (over and under the age of 50). A comparison of stroke severity, assessed by the National Institutes of Health Stroke Scale (NIHSS) score was made, whereas the functional outcome was measured by the Modified Rankin Scale Score (mRS). All parameters were evaluated both on admission and upon discharging. Women over 50 years of age were more likely to develop severe stroke - 43.3% (29), whereas no symptoms of severe stroke were observed in the male group of patients under 50 years of age. Moderate stroke symptoms were noticed in the majority of female and male patients under and over the age of 50 â€“ 29.85%(20), 46.05%(35), 50%(4), in 66.7%(4) of the examined subjects, respectively. The calculated difference of neurological deficit severity between female patients under the age of 50, female patients over 50 , male patients under50, and male patients over the age of 50, was statistically insignificant (p =0.32). Similarly, upon discharge, the preponderance of the patients from the four groups resulted with moderate neurological deficit â€“ 47.4%(18) female patients over 50 , 46.3%(19) male patients over 50, and 66.7%(4) female patients under 50 years of age. Key words : Ischemic stroke, risk factors, gender, age